2017
DOI: 10.1016/j.jtcvs.2017.04.081
|View full text |Cite
|
Sign up to set email alerts
|

Layered smooth muscle cell–endothelial progenitor cell sheets derived from the bone marrow augment postinfarction ventricular function

Abstract: Objective The angiogenic potential of endothelial progenitor cells (EPCs) may be limited by the absence of their natural biologic foundation, namely smooth muscle pericytes. We hypothesized that joint delivery of EPCs and smooth muscle cells (SMCs) in a novel, totally bone marrow-derived cell sheet will mimic the native architecture of a mature blood vessel and act as an angiogenic construct to limit post infarction ventricular remodeling. Methods Primary EPCs and mesenchymal stem cells (MSCs) were isolated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 20 publications
1
18
0
Order By: Relevance
“…The LV gradually undergoes compensatory remodeling characterized by ventricular dilatation, but ultimately fails, resulting in poor contractility and reduced cardiac output. Exogenous delivery of stem cells [8,9], engineered tissues [10][11][12][13][14], cytokines [15][16][17], and growth factors [18,19] to injured myocardium have demonstrated promising results for activating intrinsic myocardial repair pathways in various adult animal models and several human clinical trials. In response to these exogenous regenerative therapies, significant improvements in scar size and cardiac function have been observed, although complete normalization to baseline cardiac health is rare in adult animals treated at the time of MI.…”
Section: Introductionmentioning
confidence: 99%
“…The LV gradually undergoes compensatory remodeling characterized by ventricular dilatation, but ultimately fails, resulting in poor contractility and reduced cardiac output. Exogenous delivery of stem cells [8,9], engineered tissues [10][11][12][13][14], cytokines [15][16][17], and growth factors [18,19] to injured myocardium have demonstrated promising results for activating intrinsic myocardial repair pathways in various adult animal models and several human clinical trials. In response to these exogenous regenerative therapies, significant improvements in scar size and cardiac function have been observed, although complete normalization to baseline cardiac health is rare in adult animals treated at the time of MI.…”
Section: Introductionmentioning
confidence: 99%
“…SMC-EPC bi-level cell sheets secrete angiogenic factors and have potent paracrine effects [ 20 ]. In addition, these cell sheets have the ability to integrate into host vasculature and contribute to repair in an ischemic cardiomyopathy model [ 20 ]. We performed a fate tracking experiment to confirm that the same phenomenon occurs in DMCM.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, VEGF expression was preserved in animals treated with cell sheet implantation as compared to untreated animals, which may explain the higher microvascular density found in the treatment group. In addition, we previously demonstrated that transplanted EPCs and SMCs integrated into the host vasculature and exerted therapeutic effects both directly and via a paracrine-mediated pathway in a rat model of acute MI [ 18 , 20 ]. There were fewer newly-forming vessels containing transplanted cells in our rat DMCM model than in our MI model, and the cell survival rate at 4 weeks was approximately 3.7% in the DMCM model.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations